HUBUNGAN PAPARAN DEBU TERHIRUP DENGAN GANGGUAN FUNGSI PARU PADA MASYARAKAT BERISIKO DI JALAN PROF. SOEDARTO SEMARANG - Naura Sepridha Nabilla; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Semarang is one of the big cities that has a number of vehicles about 8% each year. It has an impact on increase the number of motor vehicles that descend on the highway. Street vendor, security guard, parking attendant, street sweeper, newspaper seller and tire repairer are potential to be exposed to the dust generated by motor vehicle exhaust emissions. This research aimed to analyze the association of respirable dust exposure with lung function disorder on community at risk in Prof. Soedarto Street Semarang City. This was an observational analytic research with cross-sectional design. This research was conducted in Prof. Soedarto Street Semarang City with 35 risk society determined by purposive sampling. The variables studied in this research are respirable dust exposure as independent variable and lung function disorder on community at risk in Prof. Soedarto Street Semarang City as dependent variable. To know the presence or absence of relationship beetwen of respirable dust exposure with lung function disorder on community at risk in Prof. Soedarto Street Semarang City used Chi Square test. The results of the study showed that there were 14 respondents (40%) who had respirable dust exposure above the NAB with average of respirable dust exposure was 2,49 mg/m3 and the lowest and highest dust exposure respectively 0,83 mg/m3 and 9,17 mg/m3. Result of lung fuction examination, 15 respondents had lung function disorder restriction. The results of the analysis showed a correlation of respirable dust exposure with lung function disorder (p = 0,001) and respondents with respirable dust exposure above NAB (> 3 mg/m3) had a risk 21 times greater than lung function disorder (RP 95% CI= 21,000). It can be conclude respirable dust exposure above NAB (> 3 mg/m3) had a risk to cause lung function disorder on community at risk at Prof. Soedarto Street Semarang City.